1991
DOI: 10.1073/pnas.88.10.4265
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of the electronic transitions of cytochrome c oxidase: evidence for two conformational states of ferrous cytochrome alpha.

Abstract: Second-derivative absorption spectra are re-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
1

Year Published

1992
1992
1996
1996

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 21 publications
6
31
1
Order By: Relevance
“…These solvent perturbations do not, however, significantly affect the frequencies of the Raman bands of these molecules when excited under either nonresonance or resonance conditions, although some effect on the Raman intensities has been noted (Copeland & Spiro, 1985;Hildebrandt et al, 1988). By analogy, the differences seen here in the optical spectra of cytochrome a upon complex formajion with cytochrome c, and previously seen between the liganded and unliganded forms of the reduced enzyme (Sherman et al, 1991), could be due to changes in the polarity of the protein environment immediately surrounding the heme. Such polarity changes could be brought about, for example, by movement of a charged amino acid residue or a water molecule (Sassaroli et al, 1989) into proximity with cytochrome a.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…These solvent perturbations do not, however, significantly affect the frequencies of the Raman bands of these molecules when excited under either nonresonance or resonance conditions, although some effect on the Raman intensities has been noted (Copeland & Spiro, 1985;Hildebrandt et al, 1988). By analogy, the differences seen here in the optical spectra of cytochrome a upon complex formajion with cytochrome c, and previously seen between the liganded and unliganded forms of the reduced enzyme (Sherman et al, 1991), could be due to changes in the polarity of the protein environment immediately surrounding the heme. Such polarity changes could be brought about, for example, by movement of a charged amino acid residue or a water molecule (Sassaroli et al, 1989) into proximity with cytochrome a.…”
Section: Discussionsupporting
confidence: 68%
“…We have previously shown that the second derivative absorption spectrum of ferrocytochrome a is sensitive to ligand binding events at cytochrome a3 in the purified bovine enzyme (Copeland, 1991;Sherman et al, 1991). We have further shown that ferrocytochrome c binding affects the second derivative absorption spectrum of bovine cytochrome c oxidase in its cyanide-inhibited forms, but not in its unliganded or CO-inhibited forms (Lynch et al, 1992).…”
Section: Second Derivative Absorption Spectroscopymentioning
confidence: 94%
See 1 more Smart Citation
“…Malmstriim [14] has proposed that two-electron reduction of the initially fully oxidized enzyme alters its conformation in such a way as to facilitate reduction of the a3 Cu, centre. Sherman et al [9], using second-derivative spectroscopy, suggest that the form of cytochrome a present during the steady state is different from that at full reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Toward this end, we have introduced the use of second derivative absorption spectroscopy as a means of resolving and studying the individual electronic transitions of the 2 heme groups within the protein (Copeland, 1991(Copeland, , 1993Ishibe et al, 1991;Sherman et al, 1991;Lynch & Copeland, 1992;Lynch et al, 1992). During the course of these studies we have discovered a new electronic transition of one of the hemes at ca.…”
Section: J S Felsch Et Aimentioning
confidence: 99%